The Postqualitative Turn in Physical Cultural Studies. (25th February 2019) - Ray, John
Abstract: In this autoethnographic paper I engage with feminist theories of the body, materiality and affect to illuminate the ways in which I negotiate dominant discourses of masculinity in playing football. I begin by grounding the paper within Feminist Physical Cultural Studies, and explore the post-qualitative potential of auto-ethnography as a means of exploring lived experiences. In the sections that follow, I describe my experiences of playing football and delineate the objects and intensities which I saw within an AFL assemblage. Jerseys, balls, and beer all have the potential to mark bodies as skilful, tough, masculine, or otherwise. In examining the relationships between objects and bodies, I am able to demonstrate the means through which masculinity is woven into football.